Role of JAK2/STAT3 Signaling Pathway in the Tumorigenesis, Chemotherapy Resistance, and Treatment of Solid Tumors: A Systemic Review - Mengie Ayele T; Tilahun Muche Z; Behaile Teklemariam A; Bogale Kassie A; Chekol Abebe E (Dove Medical Press, 2022)
Teklie Mengie Ayele,1 Zelalem Tilahun Muche,2 Awgichew Behaile Teklemariam,3 Achenef Bogale Kassie,1 Endeshaw Chekol Abebe3 1Department of Pharmacy, Debre Tabor University, Debre Tabor, Amhara, Ethiopia; 2Department of Physiology, Debre Tabor University, Debre Tabor, Amhara, Ethiopia; 3Department of Medical Biochemistry, Debre Tabor University, Debre Tabor, Amhara, EthiopiaCorrespondence: Endeshaw Chekol Abebe, Tel +251928428133, Email endeshawchekole@gmail.comAbstract: Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) pathway is a common signaling pathway used to transduce signals from the extracellular to the intracellular (nucleus) upon the binding of cytokines and growth factors to the extracellular domain of specific cell surface receptors. This signaling pathway is tightly regulated and has a multitude of biological functions such as cell proliferation, differentiation, and apoptosis. Besides, the regulated JAK2/STAT3 signaling plays a crucial role in embryonic development, hemopoiesis, and controlling the immune system. Conversely, aberrantly activated JAK2/STAT3 is frequently detected in varieties of tumors and involved in oncogenesis, angiogenesis, and metastasis of many cancer diseases that are usually refractory to the standard chemotherapy. However, the JAK3/STAT3 pathway recently emerged interestingly as a new site for the development of novel anti-tumor agents and becomes a promising therapeutic target in the treatment of many solid malignancies. Herein, this review aimed to provide insight into the JAK2/STAT3 pathway, in the hope to gain an understanding of its potential role in the pathogenesis, progression, chemotherapy resistance, and cancer therapy of solid tumors.Keywords: solid tumors, JAK2/STAT3 signaling, tumorigenesis, JAK2/STAT3 targeted therapy